Bone mineral density, vitamin D and anticonvulsant therapy - SILVANA FILARDI; CARLOS A.M. GUERREIRO; LUIS ALBERTO MAGNA; JOÃO FRANCISCO MARQUES NETO (Arquivos de Neuro-Psiquiatria)
The aim of this study was to assess bone mineral density and vitamin D metabolism in patients on chronic anticonvulsant therapy. METHODS: Sixty-nine men, outpatients on chronic anticonvulsant therapy, who had been treated for at least 5 years, were studied, comparing them to thirty healthy controls. Bone mineral density was measured as well as serum levels of calcium, ionized calcium, alkaline phosphatase, PTH, 25-hydroxycholecalciferol and 1,25-dihydroxycholecalciferol. RESULTS: No differences in bone mineral density, serum levels of vitamin D and intact-PTH were observed between patients and controls. Bone mineral density was not associated with chronic anticonvulsant therapy. CONCLUSION: Those adult patients who were on chronic anticonvulsant therapy and who lived in low latitude regions had normal bone mineral density as well as vitamin D serum levels.